2022
DOI: 10.3390/molecules27217510
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Characterization, and Evaluation of Eudragit-Coated Saxagliptin Nanoparticles Using 3 Factorial Design Modules

Abstract: Background and Introduction: Saxagliptin is a hypoglycemic drug that acts as a dipeptidyl peptidase-4 (DPP-4) inhibitor and is preferably used in the treatment of Type 2 Diabetes Mellitus (T2DM). It is safe and tolerable; however, the major disadvantage associated with it is its low bioavailability. Aim: The present research aimed to enhance the bioavailability of the drug by enteric coating with a polymer that controls the rate of drug delivery, and it was prepared as Solid Lipid Nanoparticles (SLNs). Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The pure ELD showed prominent functional group peaks at 3117 cm −1 (-NH- str), 3117 cm −1 (-NH-), 1696 cm −1 (-COOH), 1658 cm −1 (-RCONH2-), and 1429 cm −1 (-C=C-), which confirmed the purity of the drug [ 47 ]. The peaks at 3532 cm −1 and 3239 cm −1 (CH aliphatic stretching) were visible in the spectra of eudragit RS100 [ 48 ]. The characteristic absorption bands of ELD diminished or disappeared in the fingerprint region of the drug, which indicated that the drug encapsulated inside the eudragit polymer, and the appearance of new peaks in the ENP2 corresponding eudragit and PVA confirmed successful entrapment.…”
Section: Resultsmentioning
confidence: 99%
“…The pure ELD showed prominent functional group peaks at 3117 cm −1 (-NH- str), 3117 cm −1 (-NH-), 1696 cm −1 (-COOH), 1658 cm −1 (-RCONH2-), and 1429 cm −1 (-C=C-), which confirmed the purity of the drug [ 47 ]. The peaks at 3532 cm −1 and 3239 cm −1 (CH aliphatic stretching) were visible in the spectra of eudragit RS100 [ 48 ]. The characteristic absorption bands of ELD diminished or disappeared in the fingerprint region of the drug, which indicated that the drug encapsulated inside the eudragit polymer, and the appearance of new peaks in the ENP2 corresponding eudragit and PVA confirmed successful entrapment.…”
Section: Resultsmentioning
confidence: 99%
“…The pellet was kept in a sample holder and scanned from 4000 cm -1 to 400 cm -1 in an FT-IR spectrophotometer. The possible interaction between Haloperidol PVP K30 and Poloxamer 407 was assessed by comparing FT-IR spectra of the pure drug (Haloperidol), polymer (PVP K30) and surfactant (poloxamer 407) [26,27].…”
Section: Drug-excipients Compatibility Studies Ft-ir Spectroscopymentioning
confidence: 99%